Assessing the associations between Aedes larval indices and dengue risk in Kalutara district, Sri Lanka: a hierarchical time series analysis from 2010 to 2019 - Liyanage, Prasad; Tozan, Yesim; Tissera, Hasitha Aravinda; Overgaard, Hans J.; Rocklöv, Joacim (Parasites & vectors, 2022)
Dengue is a major public health problem in Sri Lanka. Aedes vector surveillance and monitoring of larval indices are routine, long-established public health practices in the country. However, the association between Aedes larval indices and dengue incidence is poorly understood. It is crucial to evaluate lagged effects and threshold values of Aedes larval indices to set pragmatic targets for sustainable vector control interventions.
Gesehen am 28.08.2022